Crystal structure and DNA-binding analysis of RecO from Deinococcus radiodurans - Leiros, Ingar (2005)
The RecFOR pathway has been shown to be essential for DNA repair through the process of homologous recombination in bacteria and, recently, to be important in the recovery of stalled replication forks following UV irradiation. RecO, along with RecR, RecF, RecQ and RecJ, is a principal actor in this fundamental DNA repair pathway. Here we present the three-dimensional structure of a member of the RecO family. The crystal structure of Deinococcus radiodurans RecO (drRecO) reveals possible binding sites for DNA and for the RecO-binding proteins within its three discrete structural regions: an N-terminal oligonucleotide/oligosaccharide-binding domain, a helical bundle and a zinc-finger motif. Furthermore, drRecO was found to form a stable complex with RecR and to bind both single- and double-stranded DNA. Mutational analysis confirmed the existence of multiple DNA-binding sites within the protein.